Evaluation of Compliance with the Guidelines for the Safe Use of Potassium Chloride - Fernández Bargiela, Noelia; Salvador Garrido, Pilar; Pedreira Vázquez, Isaura; González Piñeiro, Sara; Martín Herránz, María Isabel (Ars Pharmaceutica (Internet), 2017)
Objective: To analyze the degree of compliance with the “Guidelines for the safe use of potassium chloride” implemented in our hospital, using periodic audits, during the period 2013-2016. Methods: Descriptive study of the audits carried out at 6 months post-implementation (beginning of 2013) and then every year (2014-2016). The evaluation indicators were developed following the recommendations included in the Guidelines and referred to storage, prescription, preparation and administration of potassium solutions. The patient care units evaluated are: critical care authorized units (storage and independent double checks during preparation of solutions and before its administration) and all patient care units (prescription and correct labeling for its correct administration). Results: There were audited 55 patient care units, which showed a compliance of 100% for the prescription and correct labeling indicators. Of those units, 12 (critical and emergency units) are authorized to have concentrated potassium chloride ampoules 1M. These 12 units did not have a correct compliance with the other two indicators, because one unit did not show a correct storage (in 2014) and the double check required was not verified by 3 units in 2013, one in 2014 and 2015. Conclusion: The audits showed the correct follow-up with the Guidelines for most of the evaluated criteria, however demonstrated the need to carry out periodic strategies of intensification and remembrance to guarantee the correct compliance of all the established recommendations.